IMPLEMENTATION OF THE FULFILLMENT OF INMATE HUMAN RIGHTS IN CIREBON CLASS I CORRECTIONAL INSTITUTION - Gupta, Adrey Fitri Zildjian Chandra; Fadhila, Noerul Putri; Febriyanti, Ria; Usman, Usman Faith (Ann Publisher, 2025)
Abstract: Background. The fulfillment of human rights for prisoners is a crucial issue in the context of Indonesia's criminal justice system, particularly following the enactment of Law No. 22 of 2022. This law emphasizes the importance of protecting the fundamental rights of prisoners, including the right to health, education, and freedom of religion and belief. Aims. This study aims to analyze the effectiveness of implementing Law No. 22 of 2022 in fulfilling human rights for prisoners, as well as identify the obstacles encountered during this process. Methods. The research method employed in this study is a qualitative approach, focusing on interviews and secondary data analysis to explore the fulfillment of human rights in Correctional Institutions (Prisons). Result. The law employs a rehabilitative approach to create a more humane correctional environment, where inmates not only serve their sentences but are also allowed to improve themselves and prepare for community reintegration. Despite this, the implementation of this law faces various challenges, such as limited facilities, a lack of trained human resources, and the social stigma inherent in prisoners. Conclusion. With a better understanding of the challenges and opportunities in fulfilling human rights in correctional institutions, Implementation. It is hoped that this will provide constructive recommendations for improving the penitentiary system in Indonesia.